ENHANCED ULTRASOUND IMAGING APPROACH FOR DIAGNOSIS OF ANKLE MUSCULOSKELETAL DISORDERS - SINGH, VEDPAL (2017)
Musculoskeletal system comprises of bones, muscles, ligaments, joints and other connective tissues, which maintains strength and stability in human body.